124 Comparison of patients' demographics, in-hospital and 3-year mortality rates and independent predictors of death in ST-elevation vs non-ST elevation myocardial infarction—an interventional centre experience. (22nd September 2015) - Nair, S B; Chacko, S M; Dixit, A; Rishton, P; Steward, N; Rezai, R; Khattar, R S
Abstract : Introduction: Acute clinical presentations of coronary artery disease include ST elevation myocardial infarction (STEMI) and non-ST elevation myocardial infarction (NSTEMI). Whereas STEMI presentations tend to be due to persistent thrombotic coronary artery occlusion requiring immediate revascularisation, NSTEMI presentations tend to be associated with transient thrombotic occlusion and critical stenosis of the culprit vessel which may initially be managed with aggressive anti-platelet and anti-ischaemic therapy. Aims: The aim of this study was to compare the annual incidence, demographic characteristics, in-hospital mortality rates, 3-year mortality rates and independent predictors of death in patients presenting with STEMI vs NSTEMI acute coronary syndromes. Methods: We performed a retrospective study of patients admitted via our casualty department between January and December 2006, with a confirmed diagnosis of STEMI or NSTEMI. All patients had prolonged cardiac chest pain or equivalent ischaemic symptoms associated with a serum troponin T rise. Categorisation into STEMI or NSTEMI was based on typical ECG changes. The variables analysed included age, gender, ethnicity, hypertension, diabetes, hyperlipidaemia, smoking, previous ischaemic heart disease and chronic renal impairment. The rates of coronary angiography, revascularisation, in-hospital death and 3-year death were also assessed. Results: The study cohort consisted of 111 STEMI and 322 NSTEMI patients with a follow-up period of 3 years. Comparative data are given below in Abstract 124 Tables 1 and 2 : The STEMI group were younger and had a higher proportion of men and smokers, whereas the NSTEMI group had a higher prevalence of diabetes, hypertension, previous IHD and chronic renal disease. Although STEMI patients had higher coronary angiographic and revascularisation rates than NSTEMI patients, in-hospital death rates in the two groups were similar. However, the 3-year death rate was more than twofold higher in the NSTEMI compared to STEMI group. Age (p=0.007) was the only independent predictor of 3-year mortality in STEMI patients, whereas age (p<0.001) and chronic renal disease (p<0.001) were independent predictors of death in the NSTEMI group. Conclusion: In conclusion, our study demonstrates a significant difference in comorbidities, revascularisation rates and 3-year mortality rates among STEMI and NSTEMI patients. NSTEMI patients were older, had more comorbidities and higher death rates than STEMI patients. Age was the most robust independent predictor of death in both groups and chronic renal disease, when present, also asserted an adverse prognostic outcome.